Early state socialism and eugenics: Premarital medical certificates in Czechoslovakia, East Germany, and Poland in the aftermath of World War II - Jarska, Natalia; Lišková, Kateřina; Wahl, Markus (History of the Human Sciences, 2024)
The article discusses the immediate post-war persistence and subsequent rejection of eugenics in East-Central European socialist states, exploring the case of premarital medical certificates. Building our analysis on published and archival sources, we show that immediately after the war, policies formulated at the governmental level were informed by eugenic ideas in medical expertise. Premarital medical certificates were aimed at combatting contagious diseases and thus securing a healthy population. Their legal status varied: in Poland, they were formally introduced; in the Soviet Occupied Zone and East Germany, Nazi law was abolished, but local officials still advocated for the introduction of certificates; and in Czechoslovakia, medical certificates were planned but not introduced. Despite these differences, after a short period between 1949 and 1950, the attempts to put a measure into practice ended in all three countries. We argue that the communist takeover and consolidation of power played a decisive role. After 1950, premarital medical certificates were not discussed again in Czechoslovakia or East Germany; in Poland, the debate re-emerged in 1959–60 during political liberalization.
CRIS-Team Scopus Importer:2024-11-08
Keywords: counselling; expertise; marriage; medicine; state socialism

Krieg und medizinische Versorgung – ein medizinhistorischer Überblick - Wahl, Markus (Zeitschrift für medizinische Ethik, 2023)
The further developments of war and weapons also pose ever new challenges to medicine. In this article, the interactions between war and medical care and research are sketchily illustrated by means of various examples. The thesis is that war, in general, must be seen as a threat to medical progress since its focus on war-related areas means that it always neglects other aspects that could benefit the general public. Thus, war is not a good teacher of medicine, even if some developments, such as the mass production of penicillin during World War II, were accelerated.
CRIS-Team Scopus Importer:2024-12-16
Keywords: history; medical care; vulnerable groups; war